Parent brands' influence on co-brand's perception: a model-based approach. Issue 5 (6th November 2018) - Böger, Daniel; Kottemann, Pascal; Decker, Reinhold
Abstract : Purpose: This paper aims to investigate what influence the perceptions of two parent brands have on the perception of a newly formed co-brand. Furthermore, it elaborates whether respondents' evaluations of the parent brands, their familiarity towards the parent brands and their usage of the parent brands affect this influence. Design/methodology/approach: Building on both cognitive consistency and information integration theory, this paper proposes a model-based approach to quantify the parent brands' influence on the co-brand's perception. Using an empirical study with 317 respondents collected by a professional online market research firm, this paper highlights the benefits of this model-based approach. Findings: The results indicate that the perception of a co-brand arises from a weighted merge of the parent brands' perceptions. The findings further reveal that the better (worse) a parent brand's evaluation is in contrast to the other parent brand's evaluation, the more (less) familiar a parent brand is in contrast to the other parent brand, and the more (less) frequent a parent brand is used in contrast to the other parent brand, the larger (smaller) is its influence on the co-brand's perception. Originality/value: The findings shed light on the formation of a co-brand's perception which can be crucial when selecting the right co-branding partner. Additionally, by quantifying the parent brands' influence on the perception of the co-brand, this model-based approach helps brand managers to analyze co-brand pairings beforehand and select the best pairing in accordance with their goals.